El liderazgo y la comunicación del directivo, en el desarrollo organizacional del colegio técnico agropecuario Oriente Ecuatoriano, de la ciudad de Palanda, provincia de Zamora Chinchipe, período 2013 - 2014 - Guaillas Macas, Mercedes Bigail (2014)
This thesis aims to determine the incidence of leadership and managerial communication, organizational development, agricultural technical college Oriente Ecuatoriano, City Palanda province of Zamora Chinchipe period 2013 - 2014. It was a descriptive study, the methods used; inductive; analytical; synthetic survey was applied to a sample of 163 students, 124 parents and 20 teachers. Were obtained the following results: 70% of teachers, 61% of students and 64% of parents who concur in stating that if the leadership of the management influences; and 50% of teachers, 24% of students and 15% of parents indicated that the behavior of managers positively influences the work of the members of the educational community; in the same way 60% of teachers, 61% of students and 64% of parents, show that communication with management is an institutional need to maintain organizational development. After the investigation, the most important conclusion states that the executive leadership positively influences the organizational development of the school and that communication becomes a strategic need to maintain and enhance the organizational development of the institution.